El orden de fundación de actos según Husserl y Scheler: una revisión desde los valores - Alarcón, Vania (2018)
This paper deals with the hierarchical organization of the subject’s acts and their foundational ranking according to Husserl and Scheler, emphasizing emotional acts and their correlative objects –values. Husserl argues that cognitive (objectifying) acts (perception, thought-acts) found emotional acts (the evaluation or feeling of values), whereas Scheler holds that emotional acts found representations or objectifying acts. This difference refers back to key points in their own conceptions of the phenomenological method and the status of objective correlates.